The Bipolar Depression Electrical Treatment Trial (BETTER): Design, Rationale, and Objectives of a Randomized, Sham-Controlled Trial and Data from the Pilot Study Phase - Bernardo de Sampaio Pereira Junior; Gabriel Tortella; Beny Lafer; Paula Nunes; Isabela Martins Benseñor; Paulo Andrade Lotufo; Rodrigo Machado-Vieira; André R. Brunoni (Neural Plasticity)
Background. Bipolar depression (BD) is a prevalent condition, with poor therapeutic options and a high degree of refractoriness. This justifies the development of novel treatment strategies, such as transcranial direct current stimulation (tDCS) that showed promising results in unipolar depression. Methods. We describe a randomized, sham-controlled, double-blinded trial using tDCS for refractory, acutely symptomatic BD (the bipolar depression electrical treatment trial, BETTER). Sixty patients will be enrolled and assessed with clinical and neuropsychological tests. The primary outcome is change (over time and across groups) in the scores of the Hamilton Depression Rating Scale (17 items). Biological markers such as blood neurotrophins and interleukins, genetic polymorphisms, heart rate variability, and motor cortical excitability will be assessed. Twelve anodal-left/cathodal-right 2 mA tDCS sessions over the dorsolateral prefrontal cortex will be performed in 6 weeks. Results. In the pilot phase, five patients received active tDCS and were double-blindly assessed, two presenting clinical response. TDCS was well-tolerated, with no changes in cognitive scores. Conclusion. This upcoming clinical trial will address the efficacy of tDCS for BD on different degrees of refractoriness. The evaluation of biological markers will also help in understanding the pathophysiology of BD and the mechanisms of action of tDCS.